An investigation into the role of specimen geometry when undertaking tribological testing on seal fin components. (March 2022) - Zhang, Boxiu; Marshall, Matthew; Lewis, Roger
Labyrinth seal systems are used in aeroengines to seal the clearance, the understanding of the wear mechanism of labyrinth seal system is necessary to achieve better sealing performance. In this work a series of tests are conducted on a high-speed test rig capable of fin tip speeds of 100 m/s. With force and temperature measurements recorded in each case, the influence of specimen geometry is investigated. Surface examination and debris analysis is also performed using microscopy post-test. The wear mechanism was found to be influenced by fin geometry. A discrete fin was observed to trigger a more efficient material removal mechanism at both incursion conditions. Where the fin segment and ring-shaped fin leading to increased temperatures and material smearing. The heat dissipate role of fin was also observed during test where longer contact time of fin and abradable gives better heat removal performance.